Diversity of hydrocarbon-degrading bacteria in mangroves rhizosphere as an indicator of oil-pollution bioremediation in mangrove forests - Afrah Siddique (19724656) (2024)
Mangrove ecosystems, characterized by high levels of productivity, are susceptible to anthropogenic activities, notably oil pollution arising from diverse origins including spills, transportation, and industrial effluents. Owing to their role in climate regulation and economic significance, there is a growing interest in developing mangrove conservation strategies. In the Arabian Gulf, mangroves stand as the sole naturally occurring green vegetation due to the region's hot and arid climate. However, they have faced persistent oil pollution for decades. This review focuses on global mangrove distribution, with a specific emphasis on Qatar's mangroves. It highlights the ongoing challenges faced by mangroves, particularly in relation to the oil industry, and the impact of oil pollution on these vital ecosystems. It outlines major oil spill incidents worldwide and the diverse hydrocarbon-degrading bacterial communities within polluted areas, elucidating their potential for bioremediation. The use of symbiotic interactions between mangrove plants and bacteria offers a more sustainable, cost-effective and environmentally friendly alternative. However, the success of these bioremediation strategies depends on a deep understanding of the dynamics of bacterial communities, environmental factors and specific nature of the pollutants. Other Information Published in: Marine Pollution Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.marpolbul.2024.116620